Terahertz lattice dynamics of the potassium rare-earth binary molybdates. (23rd January 2017) - Poperezhai, S; Gogoi, P; Zubenko, N; Kutko, K; Kutko, V I; Kovalev, A S; Kamenskyi, D
Abstract: We report a systematic study of low-energy lattice vibrations in the layered systems KY(MoO4 )2, KDy(MoO4 )2, KEr(MoO4 )2, and KTm(MoO4 )2 . A layered crystal structure and low symmetry of the local environment of the rare-earth ion cause the appearance of vibrational and electronic excitations in Terahertz frequencies. The interaction between these excitations leads to sophisticated dynamical properties, including non-linear effects in paramagnetic resonance spectra. The THz study in magnetic field allows for the clear distinction between lattice vibrations and electronic excitations. We measured the THz transmission spectra and show that the low energy lattice vibrations in binary molybdates can be well described within the quasi-one-dimensional model. The developed model describes the measured far-infrared spectra, and results of our calculations agree with previous Raman and ultrasound studies.